Evaluation of soil compaction using the dynamic penetration index and the soil physical characteristics approach on agricultural land in the Ketonggo sub-watershed, Indonesia - Mujiyo, Mujiyo; Lestari, Audi Soekma; Komariah, Komariah; Herawati, Aktavia; Irmawati, Viviana; Romadhon, Muhammad Rizky; Hardian, Tiara; Istiqomah, Nanda Mei (Brawijaya University, 2025)
Soil compaction is one of the problems faced due to land conversion in agriculture, directly impacting land productivity. This study aimed to identify the distribution of soil density with the Dynamic Penetration Index (DPI) method, the influence of land use, and the determinants of soil compaction, and provide recommendations to control soil density on agricultural land around the sub-watershed area. This research used an exploratory descriptive method, and sample points were determined by purposive sampling. There are 45 sample points determined based on the overlay map of soil type, land use, slope, and rainfall. The low DPI class has an area of 8,227 ha (34.34%), and the very low DPI class has an area of 15,729 ha (65.65%). The highest DPI value was in the plantation land use, and the lowest was in the rice field land use. Plantations experienced soil compaction due to intensive land use without soil quality restoration. The determining factors that affect soil compaction were porosity and bulk density. High porosity means low DPI values and, therefore, low compaction. High bulk density means high DPI value and therefore high compaction. Recommendations for land management include adding organic matter and tillage using a hoe or tractor to optimize soil compaction.